The combined effects of extended feeding with a high level of Arthrospira platensis and a commercial enzyme mix or porcine pancreatin on broilers’ blood cells, plasma metabolites and liver lipid profile - Paula A. Lopes; Cristina M. Alfaia; Maria P. Spínola; Rui M. A. Pinto; José M. Pestana; Mónica M. Costa; J. C. Tavares; Miguel P. Mourato; Beatriz Tavares; Daniela F. P. Carvalho; Cátia F. Martins; Madalena Lordelo; et al. (BMC Veterinary Research)
Abstract Background The increasing global demand for sustainable and eco-friendly protein alternatives in poultry production has led to the exploitation of unconventional feed ingredients, such as microalgae. This study is novel for its exploration of the extended feeding effects (from day 7 to day 35) of a high inclusion level (15%) of Arthrospira platensis (Spirulina) in broiler chickens’ diet, either alone or supplemented with enzymes, primarily peptidases (EC 3.4). The study assessed the impact on the blood cells, metabolic status and the hepatic content of lipids, pigments and minerals. One hundred and twenty Ross 308 male chickens were distributed into 40 battery brooders, housing three birds per cage. Initially, the chickens were given ad libitum access to a standard corn and soybean meal-based diet for the first seven days. Subsequently, from day 7 to 35, they were assigned to one of four experimental diets: a control diet based on corn and soybean (control group, n = 10), a diet incorporating 15% A. platensis (SP group, n = 10), a diet incorporating 15% A. platensis supplemented with 0.025% of the commercial enzyme mix VemoZyme® P (SPV group, n = 10), and a diet incorporating 15% A. platensis supplemented with 0.10% of porcine pancreatin (SPP group, n = 10). Results The 15% inclusion of A. platensis negatively impacted the birds’ growth performance by decreasing the final body weight (p < 0.001), body weight gain (p < 0.001) and average daily feed intake (p < 0.001), while increasing the feed conversion ratio (p = 0.001). This high level of A. platensis incorporation did not change the haematological profile but raised blood lipid levels. However, these increases were successfully normalized by supplementing the diet with the enzyme mix VemoZyme® P and the porcine pancreatin. Spirulina positively altered the fatty acid composition in the liver, notably increasing n-3 PUFA content (p < 0.001) and reducing the n-6/n-3 PUFA ratio (p < 0.001). Furthermore, including A. platensis augmented the concentration of beneficial pigments with antioxidant functions, irrespective of enzyme addition. Most mineral levels remained unaffected (p > 0.05) by A. platensis. Conclusions Overall, data suggest that the impact of A. platensis on blood and liver measurements outweighs the effect of enzyme supplements, VemoZyme® P or porcine pancreatin. However, these enzyme mixtures effectively mitigated the elevated blood lipid levels induced by Spirulina. Although our findings illustrate the potential of A. platensis as an alternative protein source of nutrition for poultry, further exploration is necessary to determine the feasibility of higher incorporation levels over the long term, particularly in light of the negative effects on broilers’ growth performance.